1804 Terr. of Miss. Laws 90-91 - (:unkn) unknown (My University, 1804)
An Act Respecting Slaves, § 4: Prohibited any "Slave" from keeping or carrying any gun, powder, shot, club, weapon, or ammunition.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES